Synthesis, Separation and Anti-HIV Activity of Distereoisomers of N-[p-(4-Bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine Methyl Ester (Stampidine) - Venkatachalam, Taracad K.; Qazi, Sanjive; Uckun, Fatih M. (Arzneimittelforschung, 2006)
The distereoisomers of stampidine (STAMP, DDE-113, HI-113, N-[p-(4-bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester, CAS 217178-62-6) were separated using two different procedures. The first method involved separation of the isomers by fractional crystallization, and the second method utilized a preparative HPLC. Both isomers were active against the HIV-1 strain HTLVIIIB and neither isomer was more or less active than distereoisomeric mixture of stampidine.
Keywords: Anti-HIV agents; Antiretroviral therapy; N-[p-(4-Bromophenyl)-2',3'-didehydro-3'-deoxy-5'-thymidylyl]-L-alanine methyl ester; CAS 217178-62-6; DDE-113; HI-113; Stampidine, distereoisomers, hydrolysis, separation of isomers